In-depth Analysis of the 2022 March 28 3He-rich Solar Energetic Particle Event - Mirko Stumpo; Monica Laurenza; Simone Benella; Anna Milillo; Christina Plainaki; Matthew J. West; Pietro Zucca; Stas Barabash; Daniel Heyner; Ali Varsani; Go Murakami; Shyama Narendranath; et al. (The Astrophysical Journal)
On 2022 March 28, a solar eruption from active region AR 12975 produced a solar energetic particle (SEP) event observed by BepiColombo (BC; 0.57 au), STEREO-A (STA; 0.97 au), GOES (1.0 au), ACE (L1), and Wind (L1). The event was associated with an M4.0 soft X-ray flare peaking at 11:29 UTC, a Type III radio burst (0.1–16 MHz) at 11:24 UTC, a metric Type II radio burst (25–250 MHz) at 11:23 UTC, and a coronal mass ejection with a speed of 700 km s ^−1 . BC and STA, magnetically aligned along the same Parker spiral and well connected to the flare site (footpoint separations of 19 $\mathop{.}\limits^{\unicode{x000b0}}$ 8 and 16 $\mathop{.}\limits^{\unicode{x000b0}}$ 5, respectively), detected a gradual SEP event with remarkable impulsive characteristics, including a high ^3 He/ ^4 He ratio (0.7 at 1 MeV), elevated Fe/O ratio (∼0.5 increasing with energy), a ^3 He spectrum harder than that of other ions, and particle dropouts at BC linked to intermittent magnetic connections. Near-Earth spacecraft (44 $\mathop{.}\limits^{\unicode{x000b0}}$ 8 from the flare site) observed abundance ratios closer to coronal values, and more uniform proton/heavy-ion spectra. Our findings suggest both the contribution of particles accelerated by a quasi-parallel shock and a direct contribution from flare suprathermals, accelerated during postflare ongoing reconnection, at well connected spacecraft.